2019
DOI: 10.7770/safer-v0n0-art1549
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heavy metals in some locally produced food seasonings in Katsina State Nigeria

Abstract: This study was conducted to determine the heavy metals concentration in seeds used as raw materials in producing local food seasonings (Locust bean, Soya beans and seed of Hibiscus subdariffa) and the produced local seasonings (Daddawar Kalwa, Daddawar waken Soya and Daddawar Botso) in Katsina state Nigeria. The objectives were mainly to detect the presence of heavy metals in some local seeds used in the preparation of local seasonings and their processed products used in food seasoning in the study ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Although a previous study from Katsina State, Nigeria [8] has reported the heavy metal Ni to be below detection level (BDL) in fish samples, with similar studies conducted in the state in legumes, cereals and vegetables corroborating the same finding [38][39][40][41][42][43]. The present study is among the few of such studies [44,13] that reported a detection of Ni in evaluated food samples.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Although a previous study from Katsina State, Nigeria [8] has reported the heavy metal Ni to be below detection level (BDL) in fish samples, with similar studies conducted in the state in legumes, cereals and vegetables corroborating the same finding [38][39][40][41][42][43]. The present study is among the few of such studies [44,13] that reported a detection of Ni in evaluated food samples.…”
Section: Resultssupporting
confidence: 85%
“…The risk assessment for carcinogenic exposure effect has revealed that the incremental lifetime cancer risk (ILCR) and the cumulative lifetime cancer risks (∑ILCR) were all above the safe limit for cancer in the children population with the heavy metal Ni contributing the highest risk and the sample of the fish sample of Clarias gariepinus having the highest cancer risk (Tables 6). [38][39][40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…This is an indication that, it can pose a threat of cancer risk to the population living in the area. Earlier studies on heavy metal cancer risks in various food samples conducted in Katsina State have implicated heavy metals in the food samples as possible contributors to the population cancer burden [41,42,43].…”
Section: Cancer Risksmentioning
confidence: 99%